Pharmacology and Toxiclogy of Echinacea, Souroubea and Platanus spp. - Liu, Rui (Université d'Ottawa / University of Ottawa, 2019)
The research presented in this thesis addressed knowledge gaps for three medicinal plant taxa, Souroubea spp. (Marcgraviaceae) and Platanus (Platanaceae) as well as Echinacea spp. (Asteraceae). The primary pharmacological mechanism of Souroubea sympetala and Platanus occidentalis were well established, with pentacyclic triterpenes identified as major active principles. My results indicate that major triterpenoids, and crude plant extracts, selectively inhibited monoacyglycerol lipase (MAGL) activity but not fatty acid amide hydrolase (FAAH) activity. These data suggest a possible secondary anxiolytic mechanism of action through the endocannabinoid system (ECS). My study of herb-drug interactions of Souroubea and Plantanus products showed some potential risk when combined with a classic benzodiazepine class drug, diazepam, and I proposed a mechanism through in vitro CYP450 enzyme inhibition. The pharmacokinetic study revealed the difficulty of detecting betulinic acid in animal blood. To support the development a commercial botanical composed of these medicinal plants, an extraction method and a highly sensitive and selectivity HPLC-APCI-MS based quantification method was successfully developed and validated. Part II of this thesis focused on the impact of phytochemical variation and hepatic metabolism on the ECS activity of Echinacea spp. and explored the potential for new applications of Echinacea spp. as a natural health product. My research indicated that considerable variability in the content of phenolic and alkylamide (AKA) compounds reflected similar variability in in vitro bioactivity at ECS-related pharmacological targets. Following biochemometric analysis, several phenolic compounds and AKAs in Echinacea spp. were found to be significant independent variables determining FAAH inhibition and CB receptor activation. Hepatic metabolism was also found to affect the FAAH inhibition of AKA, as increased FAAH inhibitory effects were observed after CYP450-mediated metabolism of both individual AKAs and crude extracts of E angustifolia and E. purpurea, suggesting a “pro-drug” mechanism. Dose dependent activities were observed with oral administration of both E angustifolia and E. purpurea root extract in rat paw model of inflammation and pain. Further tests indicated these activities can be partially blocked by co-administration of CB1 and CB2 receptor antagonists AM251 and AM630, respectively. This evidence suggests activity for peripheral pain was at least partially mediated through the ECS.
Keywords: Natural health products; Endocannabinoid system; Phytochemistry; Herb-Drug interaction